The inclusive teachers between theory and practice - Zanazzi, Silvia (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2019)
Starting from the Profile of inclusive teachers by the European Agency for Special Needs and Inclusive Education and its fundamental values, this article will describe the partial results of a research project that is being carried out in three high schools. The research, adopting a phenomenological approach, aims to investigate and understand the factors favouring or hindering inclusion in the daily life of teachers and teaching assistants, analyzing the opinions and beliefs of all stakeholders. So far, 49 indepth interviews have been administered; data collection will continue during the 2018 - 2019 school year, also through focus groups and direct observations, so to investigate the theme under different viewpoints, including as many perspectives as possible. The article describes the areas of convergence and non-convergence among the fundamental values of the Profile and those emerging from the interviews with teachers, with the aim of highlighting the deeply rooted inclusive values on the one hand, and the problems and the areas that need to be strengthened on the other.